2020
DOI: 10.9734/ajarr/2020/v8i230195
|View full text |Cite
|
Sign up to set email alerts
|

Association of Innovative Work Behaviour, Organizational Frustration and Work-family Conflict among Private Sector Employees

Abstract: Private sector is so challenging and demanding owing to market competitions and unfavorable work environment which frustrate employees’ efforts. Against this backdrop, this study explored the association of innovative work behavior, organizational frustration and work-family conflict among employees of Innoson Technical and Industrial Company Ltd Emene, Enugu, Nigeria. The sample population of the study comprised 112 private sector workers (89 males and 23 females) with age range from 23-56 years with a mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Organizational climate may support employees' innovative behaviour as well as create a frustrating atmosphere or even lead to work-to-family conflict (Ezeh et al 2020). In job outcomes, organizations are often faced with problems of counterproductive behaviours among their employees; however, the threat posed by counterproductive workplace behaviour is very inimical to any organizations' drive towards sustainable growth.…”
Section: Reviewmentioning
confidence: 99%
“…Organizational climate may support employees' innovative behaviour as well as create a frustrating atmosphere or even lead to work-to-family conflict (Ezeh et al 2020). In job outcomes, organizations are often faced with problems of counterproductive behaviours among their employees; however, the threat posed by counterproductive workplace behaviour is very inimical to any organizations' drive towards sustainable growth.…”
Section: Reviewmentioning
confidence: 99%
“…So, if the lecturer loses space and time to think, he/she will be less innovative. Supporting this assumption, previous studies revealed that the role conflict is negatively related to employee innovative work behaviors [19][20][21]. Further, the increased workload will decrease the innovation potential of employees [22].…”
Section: Literature Review Job Demands-resources Modelmentioning
confidence: 84%
“…This is in line with the findings of previ-ous studies. Role conflict has a negative effect on employees' innovative behavior [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research indicates that work-family role conflict decreases the probability of individuals engaging in innovative behavior (Choi et al, 2017b;Rafsanjani et al, 2021;Van Dyne et al, 2002). Furthermore, previous research show that role conflict has a negative effect on employee innovative behaviors (Chen et al, 2018;Choi et al, 2017a;Ezeh et al, 2020). The scarcity model also revealed a similar situation, too many roles lead employees to experience role conflict due to lack of energy and time (Moore, 1963).…”
Section: Work-family Conflict (Wfc)mentioning
confidence: 94%